Effectiveness Combination of Ginger Extract (Zingiber officinale) and Ranitidine Compared with Combination of Ranitidine and Placebo against Severity of Functional Dyspepsia - Dite Ari Prapti; Neneng Ratnasari; Siti Nurdjanah (Faculty of Medicine Universitas Gadjah Mada, 2017)
ABSTRACTBackground: Efficacy ranitidine as dyspepsia functional treatment was 8-35 % and ginger extracts as a traditional recipe in various countries for generations could be used as a therapy dyspepsia, antinausea, spasm, colic, and other stomach complaints. Ginger therapeutic effectiveness could reach 68-77% in vivo studies (animal models).Objective: To determined how much influence combination of ginger extract and ranitidine could improve severity of dyspepsia compared with combination of ranitidine and placebo in patients with functional dyspepsia.Method: This study was a quasi experimental. The research was conducted from December 2015 until April 2016 with 26 participants.Results: After getting therapy for 2 weeks in group I, mean SODA score in the pain scale decreased (8.4 %) of 29.07 ± 7.29 to 25.08 ± 8.22, statistically significant (p <0.046). Mean SODA score in the pain scale group II decreased (7.2%) of 25.38 ± 6.19 to 24 ± 6.01 (p=0.302). Mean SODA score in the non pain scale in group I decreased (7.7%) of 16.84 ± 2.44 to 15.15 ± 2.64 (p=0.074), while in the group II decreased (1.6%) of 15.77 ± 2.71 to 15.23 ± 2.94 (p=0.470). Mean SODA score in the satisfaction scale in group I increased (19.9%) of 7.77 ± 3.63 to 10.08 ± 3.59 (p=0.053) while in the group II increased (8.4%) of 9.62 ± 2.72 to 10.92 ± 2.46 (p=0.072). Comparison decline of SODA score in the pain scale between group I was 4.31 ± 6.3 and in group II is 1.23 ± 4.91, greater in group I but not significantly (p=0.178) at baseline to week 2nd. Comparison decline of SODA score in the non pain scale between group I was 1.69 ± 3.11 and in group II was 0.54 ± 2.6, greater in group I but not significantly (p=0.316) at baseline to week 2nd. Comparison increasing of SODA score in the satisfaction scale between group I was – 2.31 ± 3.88 and in group II was -1.31 ± 2.39, greater in group I but not significantly (p=0.437). Conclusion: Combination of ginger extract and ranitidine could decrease pain scale, non pain scale and increase satisfaction scale more effective clinically than plasebo and ranitidine for functional dyspepsia patient, but not statistic significantlyKeywords: ginger extract, severity of dyspepsia, and functional dyspepsia